Gut Microbiota and Immunotherapy - Xu, Xiaoqing; Ying, Jieer (Frontiers in Microbiology, 2022)
The gut microbiota is the largest microbiota in the body, which is closely related to the immune state of the body. A number of studies have shown that gut microbiota and its metabolites are involved in host immune regulation. Immune checkpoint inhibitors have become an important drug for the treatment of many malignant tumors, which can significantly improve the prognosis of tumor patients. However, a considerable number of patients cannot benefit from immune checkpoint inhibitors. At present, the known treatment methods of microbiota manipulation mainly include fecal microbiota transplantation, dietary regulation, prebiotics and so on. Therefore, this paper will discuss the possibility of improving the anti-tumor efficacy of immunotherapy from the perspectives of the gut microbiota and immunotherapy.